Global Research Trends on Learning Media in Quality Education: Bibliometric Analysis - Husain, Andi Musthafa; Rahmiwati; Dinar Pratama; Binti Anisaul Khasanah; Suparman (Unisia, 2025)
This study aims to analyze global trends in learning media research in supporting the achievement of quality education in line with the Sustainable Development Goals (SDGs). Using a bibliometric analysis method, this study examines 13,246 publications from 2000 to 2024 obtained through the Dimensions database. The article selection process uses the PRISMA method, focusing on publications relevant to the keywords "Learning Media" and "Quality Education". The findings reveal a significant increase in the number of publications and citations related to learning media, especially during the 2019-2022 period, driven by the need for online learning during the COVID-19 pandemic. Collaborative network analysis among researchers reveals the existence of major collaboration groups, with several key researchers significantly contributing to the development of this topic. The co-occurrence visualization of terms also identifies three main themes in learning media research: learning outcomes, learning activities, and technology-based media development. This study highlights the critical role of learning media in supporting quality education and its contributions to other SDG goals, such as innovation and reducing educational access inequality. The implications of these findings emphasize the need for further in-depth research on the long-term impact of learning media and the importance of sustainability and accessibility of such media to achieve inclusive and equitable education.